Construction and Practice of Higher Vocational Education in E-sports and Management Major - Li, Wenfang (International Journal of Social Sciences and Public Administration, 2025)
The core concept of vocational education lies in its emphasis on practicality, career orientation, and close connection with the industry. However, currently higher vocational education has not been able to effectively meet the needs of society, nor has it been able to meet the individual self actualization requirements of students. Therefore, higher vocational education needs to strengthen research on industry demand, adjust and optimize professional settings in a timely manner, and ensure close connection with the market. At the same time, schools should focus on improving students’ professional ethics and practical abilities, providing better support for their smooth integration into the workplace. Only in this way can we better meet the demand for talent in society and promote a positive interaction between vocational education and industrial development.